KEMAMPUAN PEMAHAMAN KONSEP KIMIA PADA PEMBELAJARAN DARING BERDASARKAN STIMULUS TANGGAPAN DAN EVALUASI TERHADAP HASIL BELAJAR - Siti Suryaningsih; Nur Sirril Hayat (Lantanida Journal, 2022)
This study aims to describe 1) the validity, reliability, and distribution of research instrument data; 2) students' perceptions of the ability to understand chemical concepts in online learning based on indicators of stimulus, response, and evaluation of learning outcomes. Descriptive quantitative research method, data collection on 19 SMAITA students was selected by purposive sampling. Perception data was obtained through a questionnaire in the form of a google form containing 3 indicators and post-test data in the form of UTS scores. The results showed that the questionnaire instrument was valid and reliable as evidenced by the corrected item-total correlation of 9 statements, each of which had a value of more than 0.3 and a reliability value of 0.722 and the data were normally distributed. Perceptions of the ability to understand chemical concepts in online learning based on stimulus indicators 39.5% agree, 11.85% strongly agree and 47.32% are neutral. Perception-based on response indicators 63.17% agree 5.3% strongly agree. And Perception based on evaluation indicators 81.6% agree 13.15% strongly agree. The majority of students actively ask questions when there are unclear questions, can better understand the material after having discussions, become more confident when answering UTS questions, feel suitable for online chemistry learning during the pandemic but online learning is not accompanied by other media such as youtube which is less attractive. The results of this study can be used as a scientific reference for the online learning process.